A role for the International Monetary Fund in economic development - BIRD, G. (PSL Quarterly Review, 2013)
The work argues that while much of the International Monetary Fund’s traditional role in overseeing the international financial system has disappeared, at least temporarily, its role in fostering world economic development has taken on a new urgency and importance. By providing financial assistance to those largely non-oil developing countries in deficit, the Fund can complement the private international banks and increase the stability of the world’s financial system. The author briefly summarises the existing situation and identifies some of its weaknesses before putting forward suggestions to remedy these deficiencies and examining their implications. JEL: G23, F33, F35